2001
DOI: 10.2307/1552214
|View full text |Cite
|
Sign up to set email alerts
|

The N-Factor in Natural Landscapes: Variability of Air and Soil-Surface Temperatures, Kuparuk River Basin, Alaska, U.S.A.

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. INSTAAR, University of Colorado andThe Regents of the University of Colorado, a body corporate, contracting on behalf of the University of Colorado at Boulder for the benefit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
132
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(139 citation statements)
references
References 12 publications
6
132
0
1
Order By: Relevance
“…N factors, which were originally developed by engineers as a way of estimating the freezing and thawing depth (Carlson, 1952;Lunardini, 1978), have also been applied in many studies of the natural environment (Jorgenson and Kreig, 1988;Kade et al, 2006;Karunaratne and Burn, 2004;Klene et al, 2001;Taylor, 1995). The n factor, Eq.…”
Section: Discussionmentioning
confidence: 99%
“…N factors, which were originally developed by engineers as a way of estimating the freezing and thawing depth (Carlson, 1952;Lunardini, 1978), have also been applied in many studies of the natural environment (Jorgenson and Kreig, 1988;Kade et al, 2006;Karunaratne and Burn, 2004;Klene et al, 2001;Taylor, 1995). The n factor, Eq.…”
Section: Discussionmentioning
confidence: 99%
“…They report differences of less than 2 K between the two sets of measurements under clear-sky conditions, with occasionally larger differences when clouds are not properly detected in the MODIS LST product. Validations with thermal infrared radiometers made on several homogeneous sites within a 1 km pixel area, revealed that the differences found between the LST and the field-based radiometer measurements come from essentially two sources: undetected clouds (Westermann et al, 2011) and surface heterogeneity within the pixel (Klene et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Although air temperature produces inaccurate and low-resolution estimates of ground surface temperature (GST, defined as the surface or near-surface temperature of the ground (bedrock or surficial deposit) and measured in the uppermost centimetres of the ground), it was still widely used in practical applications because of limited GST observations. In these studies, the N factor has been the most effective way to transform the air temperature to the GST (Lunardini, 1978;Klene et al, 2001). With the recent development of infrared remote sensing technology, an increasing number of land surface temperature (LST, defined as the average temperature of an element of the exact surface of the Earth (e.g.…”
Section: Introductionmentioning
confidence: 99%